The Influence of Organizational Culture and Work Stress on Work Satisfaction of The Employee (Study of University of Brawijaya Malang) - Hakim, Luthfi; Irawanto, Dodi W. (Jurnal Ilmiah Mahasiswa FEB, 2014)
The objective of research is to analyze the influence of organizational culture and work stress on work satisfaction of the employee of University of Brawijaya Malang. The expected result is whether organizational culture and work stress influence work satisfaction. The supportive organizational culture and the appropriate management of work stress will give good impact on work satisfaction of the employee. Research design is causal (cause and effect) which aims at explaining the causal relationship between research variables through hypothesis testing. Data of research are obtained through interview with informants, questionnaire and observation. The sample includes 104 respondents. Method to collect data from respondents is questionnaire with Likert Scale. Data analysis involves classical assumption test and multiple linear regression analysis. The processing of data is facilitated by SPSS Version 21 to understand the influence of organizational culture and work stress on work satisfaction of the administration employee of University of Brawijaya Malang. Independent variables in this research are organizational culture (X1) and work stress (X2), while dependent variable is work satisfaction (Y). Result of research based on the analysis over the data and the hypothesis testing has indicated that organizational culture (X1) and work stress (X2) are simultaneously and partially influencing significantly on work satisfaction (Y). One independent variable with the dominant influence on dependent variable is work stress (X2). It means that work stress experienced by the employee of University of Brawijaya Malang shall be minimized through manners and methods available to increase work satisfaction felt by the employee of University of Brawijaya Malang.